2008
DOI: 10.1080/02699050802491271
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neurobehavioural disability: A review of existing measures and recommendations for a comprehensive assessment tool

Abstract: The authors propose, promote and encourage the development of further measures with improved reliability and validity to help ensure that the unique characteristics of NBD are captured more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 59 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, the subactivity with the highest value of ICT was Supervision Time. This is known to be a major component of ICT for adults with neurological disability [ 27 ] and is required when patients are at risk of harming themselves because of either physical or cognitive loss of autonomy. This large amount of informal caregiving time found here raises concerns because it is unpaid and is frequently delivered by working-aged IC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the subactivity with the highest value of ICT was Supervision Time. This is known to be a major component of ICT for adults with neurological disability [ 27 ] and is required when patients are at risk of harming themselves because of either physical or cognitive loss of autonomy. This large amount of informal caregiving time found here raises concerns because it is unpaid and is frequently delivered by working-aged IC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations of this method, several authors still recommended estimating the pre-morbid level of functioning by asking the informant (a caregiver) to retrospectively rate the patients on measures of behavioural problems [e.g. [21]]. This retrospective assessment of behavioural changes actually remains the most common method to obtain information about the degree of changes from the pre-morbid to the current behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…We used questionnaires completed by the caregivers only because lack of awareness may constitute a threat to the validity of a questionnaire completed by the patients themselves [see [9,21]].…”
Section: Methodsmentioning
confidence: 99%
“…However, a systematic review by Cusimano et al 18 reported that the Aggression subscale did not correlate with the reference test used, suggesting inadequate construct validity for this subscale. In addition, in a recent review, Wood et al 19 argued that subsequent investigations of the factor structure of the NFI showed some variation from that originally identified, suggesting structural validity problems. In light of the widespread use of NFI, these reports are concerning and indicate a need of further refinement of the NFI subscales.…”
mentioning
confidence: 99%
“…The findings suggesting issues with structural validity of the NFI 19 involved comparing results from 2 analytical approaches, namely, principal components analysis (PCA) and confirmatory factor analysis (CFA). In PCA, the variables are experientially associated, thus sample dependent.…”
mentioning
confidence: 99%